2020
DOI: 10.20895/infotel.v12i4.547
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Analysis of K-Nearest Neighbor and Naïve Bayes Algorithm in the Diagnosis of Breast Cancer

Abstract: In the medical field, there are many records of disease sufferers, one of which is data on breast cancer. An extraction process to fine information in previously unknown data is known as data mining. Data mining uses pattern recognition techniques such as statistics and mathematics to find patterns from old data or cases. One of the main roles of data mining is classification. In the classification dataset, there is one objective attribute or it can be called the label attribute. This attribute will be searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…As shown by [17], [18], the KNN algorithm is used to identify heart disease. According to [10], NB and KNN are used in the diagnosis of breast cancer. In another paper [19], behavior determinant-based cervical cancer early detection using NB and LR.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by [17], [18], the KNN algorithm is used to identify heart disease. According to [10], NB and KNN are used in the diagnosis of breast cancer. In another paper [19], behavior determinant-based cervical cancer early detection using NB and LR.…”
Section: Related Workmentioning
confidence: 99%
“…Several classifying algorithms have been used in the analysis of medical diagnosis without feature selection. They include support vector machines (SVMs) used by [3], [4] random forests (RF) in [5], [6], k nearest neighbors (KNN) used by [7], [8], decision trees (DT) exploited in [7], [9], naive Bayes (NB) in [10], and logistics regression (LR) in [11]. Even though many studies have been done and reported in the literature, there is still room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…F. Klasifikasi Klasifikasi adalah salah satu topik data mining yang paling populer untuk mencari informasi dan banyak digunakan untuk menentukan suatu keputusan dengan pengetahuan baru yang diperoleh dari pengolahan data masa lalu menggunakan suatu algoritma (Ananda & Prasetiadi, 2021;Handayani & Ikrimach, 2020;Nuklianggraita et al, 2020) Pada penelitian ini, proses klasifikasi dilakukan dengan menggunakan cross-validation untuk membagi dataset menjadi dua set yaitu data training dan data testing serta menerapkan metode klasifikasi KNN.…”
Section: C) Varianceunclassified
“…Further research has also been carried out by [6], [7] who conducted research on the comparative analysis of the naïve Bayes Classifier and K-Nearest Neighbor methods against data classification, with the Naive Bayes method, the k-nn algorithm, confusion matrix, with the results of the comparison of the two methods. It can be concluded that the k-NN method has better accuracy than the NBC method.…”
Section: Introductionmentioning
confidence: 99%